Acute respiratory distress syndrome triggered by marked cytokine storm in a subject with diabetic ketoacidosis: A case report. Issue 12 (25th March 2022) - Horiya, Megumi; Anno, Takatoshi; Shigemoto, Ryo; Koyama, Katsumasa; Kawasaki, Fumiko; Tomoda, Koichi; Kaku, Kohei; Kaneto, Hideaki
Abstract: Rationale: Acute respiratory distress syndrome (ARDS) is an acute diffuse inflammatory lung injury. Many causes of acute direct and indirect lung injury have been described as possible initiators of ARDS. According to the literature data, ARDS could be a rare complication associated with the acute onset of diabetic ketoacidosis (DKA). Moreover, it has been suggested that cytokine release during DKA is involved in the above-mentioned acute clinical complications of DKA. Patientconcerns: A 48-year-old Japanese woman with a 4-year history of type 1 diabetes mellitus was brought to an emergency room with symptoms of deteriorated consciousness. Three days before, she was diagnosed with influenza A infection. Diagnosis: Inflammation markers were markedly elevated and she was under DKA condition. Since her respiratory conditions were suddenly and markedly aggravated 2 days later, we diagnosed her as ARDS and continued systemic management with the ventilator. Interleukin-6 (IL-6) level was markedly elevated at the onset of ARDS, although IL-6 level was high at the onset of DKA. ARDS was suggested to be caused by marked cytokine storm and DKA. Interventions: We continued to treat her hyperglycemic crises. Moreover, we continued systemic management with the ventilator. Outcomes: Approximately three weeks later, her general conditions were stabilized and ventilator management was stopped. We successfully treated her ARDS and hyperglycemic crises. Lessons: This case is very important because it shows that DKA can induce cytokine storm, which leads to the onset of ARDS. Therefore, monitoring various cytokines such as IL-6, which are associated with ARDS during the period of treatment of DKA is beneficial.